2013
DOI: 10.1039/c2em30586k
|View full text |Cite
|
Sign up to set email alerts
|

Role of macropore flow in the transport of Escherichia coli cells in undisturbed cores of a brown leached soil

Abstract: The objective of this work was to evaluate the transport of Escherichia coli cells in undisturbed cores of a brown leached soil collected at La Côte St André (France). Two undisturbed soil cores subjected to repeated injections of bacterial cells and/or bromide tracer were used to investigate the effect of soil hydrodynamics and ionic strength on cell mobility. Under the tested experimental conditions, E. coli cells were shown to be transported at the water velocity (retardation factor close to 1) and their re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…clay-dominated geology), given the same rainfall event, a proportionally greater volume of water is likely to flow over the surrounding floodplain soil, picking up soil particles and associated microorganisms before reaching a receiving stream or river. Microbial size (Gannon, Manilal, & Alexander, 1991) and cell surface characteristics, as well as soil properties (Huysman & Verstraete, 1993) and the presence of preferential flow pathways in the soil such as macropores (Martins et al, 2013) could affect the size and composition of the transported community. In addition to geology, magnitude and duration of rainfall event, and time of year are also important; greater volumes of runoff will enter streams following high-intensity and/or long-duration storm events especially when antecedent soil moisture deficit is low (Heppell et al, 2002).…”
Section: (1) Community Coalescence In Headwatersmentioning
confidence: 99%
“…clay-dominated geology), given the same rainfall event, a proportionally greater volume of water is likely to flow over the surrounding floodplain soil, picking up soil particles and associated microorganisms before reaching a receiving stream or river. Microbial size (Gannon, Manilal, & Alexander, 1991) and cell surface characteristics, as well as soil properties (Huysman & Verstraete, 1993) and the presence of preferential flow pathways in the soil such as macropores (Martins et al, 2013) could affect the size and composition of the transported community. In addition to geology, magnitude and duration of rainfall event, and time of year are also important; greater volumes of runoff will enter streams following high-intensity and/or long-duration storm events especially when antecedent soil moisture deficit is low (Heppell et al, 2002).…”
Section: (1) Community Coalescence In Headwatersmentioning
confidence: 99%
“…It was notable that intermittent spray irrigations in the autumn were generally more effective for retention than single drip irrigation events, indicating that intermittent irrigation does not have a negative impact on the filter capacity, as compared to a single irrigation event. Contradictory findings have been reported (section 5.3.3), for example by Martins et al (2013), who found that preferential transport of E. coli K-12 became more pronounced as a result of repeated injection/infiltration and drainage cycles. Further, results suggested that intermittent and drip irrigation was more effective for bacterial attenuation than steady-state flux (Table 2).…”
Section: Reduction In Undisturbed Lysimetersmentioning
confidence: 74%
“…Coherently, Jiang (2010) found that the soil saturation decreased and that the hydraulic conductivity increased after cycles of imbibitions and drainage, indicating that preferential flow paths had been formed as a result of the irrigation. In undisturbed cores Martins et al (2013) reported that E. coli K-12 breakthrough curves became bi-modal with time as a result of repeated injection/infiltration and drainage cycles. The flow regime had thus gone from uniform flow to preferential flow dominated, and porosimetry showed that this was related to local soil compaction and the formation of macropores; further, it was argued that the most important influencing factor of bacterial transport is the soil structure and its hydraulic properties (Martins et al, 2013).…”
Section: Initial Moisture Content and Infiltration Ratesmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, breakthrough curves for solutes and microbes in soils frequently exhibit early arrival and concentration tailing or multiple peaks (e.g., Wang et al, 2013). Transport models of varying complexity have been developed to simulate nonequilibrium flow and transport processes (Dhawan et al, 1993; McGechan and Vinten, 2003, 2004; Gharasoo et al, 2012; Guzman and Fox, 2011; Martins et al, 2013). Detailed reviews on nonequilibrium flow and transport models are available in the literature (Jarvis, 2007; Šimůnek and van Genuchten, 2008; Köhne et al, 2009) and are only briefly outlined below.…”
Section: Alternative Modelsmentioning
confidence: 99%